A systematic review on integrating environmental sustainability in English Language Teaching: strategies for Sustainable Development Goals - C. T., Dhanyamol; N., Sethunarayanan (Frontiers in Education, 2025)
The study explores the integration of environmental sustainability in English Language Teaching (ELT) curriculum. Through a systematic review of 56 peer reviewed articles, conference publications and case studies between 2018 and 2024, the study presents the sustainability practices in English Language Teaching by examining the current practices, methods, and challenges. Data were collected from Scopus, Web of Science and Education Resources Information Center (ERIC) using search engines such as Google, Google Scholar and Semantic Scholar. Findings reveal that empirical studies dominate the research landscape, highlighting innovative approaches such as Eco-ELT, Environmental Education (EE) and Content and Language Integrated Learning (CLIL). However, challenges such as limited resources, alignment issues between sustainability and language-learning objectives, and inadequate teacher training persist. The research identifies key strategies such as interdisciplinary curriculum design, project-based learning, and the use of authentic environmental texts to enhance both language proficiency and environmental awareness. The study underscores the importance of developing open educational resources, specialized teacher training, and eco-literacy frameworks to overcome these barriers. Finally, the research calls for further interdisciplinary studies and policy support to enhance sustainability integration in language education.